The Influence of Village Funds, The Number of Bumdes, GDP And Unemployment on Community Welfare in West Nusa Tenggara Province - Purnama, Baiq Herda; Wijimulawiani, Baiq Saripta; Wafik, Ahmad Zaenal (West Science Business and Management, 2025)
This study aims to determine the partial and simultaneous effects of village funds, the number of Village-Owned Enterprises (BUMDes), Gross Regional Domestic Product (GRDP), and unemployment on the welfare of the community in the Province of West Nusa Tenggara. The research employs a quantitative method, with data analysis using a panel data regression model. This study utilizes secondary data, which combines a seven-year time series and cross-sectional data from eight regencies in West Nusa Tenggara Province. The results indicate that village funds, the number of BUMDes, and unemployment have a significant effect on community welfare. However, GRDP does not have an effect on community welfare. Furthermore, village funds, the number of BUMDes, GRDP, and unemployment collectively influence community welfare in West Nusa Tenggara Province.